Acetylation dictates the morphology of nanophase biosilica precipitated by a 14‐amino acid leucine–lysine peptide. (28th December 2016) - Lutz, Helmut; Jaeger, Vance; Bonn, Mischa; Pfaendtner, Jim; Weidner, Tobias
Abstract : N‐terminal acetylation is a commonly used modification technique for synthetic peptides, mostly applied for reasons of enhanced stability, and in many cases regarded as inconsequential. In engineered biosilification – the controlled deposition of silica for nanotechnology applications by designed peptides – charged groups often play a deciding role. Here we report that changing the charge by acetylation of a 14‐amino acid leucine–lysine (LK) peptide dramatically changes the morphology of precipitated biosilica; acetylated LK peptides produce nano‐spheres, whereas nano‐wires are precipitated by the same peptide in a non‐acetylated form. By using interface‐specific vibrational spectroscopy and coarse‐grained molecular simulations, we show that this change in morphology is not the result of modified peptide–silica interactions, but rather caused by the stabilization of the hydrophobic core of peptide aggregates created by the removal of a peptide charge upon acetylation. These results should raise awareness of the potential impact of N‐terminal modifications in peptide applications. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Manipulation of the charge of mineral peptides by N‐terminal acetylation can dramatically change the morphology of precipitated biosilica. For leucine‐lysine peptides, silica structures go from nanowires to micro‐spheres.